Primary Signet Ring Cell Carcinoma of the Prostate - Warner, Jonathan N. (Mayo Foundation for Medical Education and Research, 2010)
Nine patients treated with primary signet ring cell carcinoma of the prostate were identified among 29,783 cases of prostate cancer evaluated at Mayo Clinic from January 15, 1970, until January 2, 2009. A PubMed search of the English-language literature published from January 1, 1980, to January 1, 2010, was then performed using the key words signet ring cell and prostate, identifying 42 cases. This study reviews those cases, along with the additional 9 reported herein, and evaluates clinical characteristics, histologic diagnoses, treatment modalities, and outcomes. Mean age at diagnosis was 68 years (range, 50-85 years), and mean prostate-specific antigen level was 95.3 ng/mL (range, 1.9-536.0 ng/mL; to convert to μg/L, multiply by 1). Most patients (66%) had non–stage IV carcinoma, the most common Gleason sum was 8 (33%), and mean survival was 29 months. The presence of a primary signet ring cell carcinoma of the prostate was best confirmed by negative findings on gastrointestinal work-up, a positive stain for prostate-specific acid phosphatase, and negative carcinoembryonic antigen test results.